The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.3923/pjn.2004.268.272
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Various Doses of Cinnamon on Blood Glucose in Diabetic Individuals

Abstract: The effect of cinnamon doses on blood serum glucose was studied in type 2 diabetic individuals for 60 days. Sixty type 2 diabetic individuals of both sexes and of age 48±6.5 years were divided into 6 groups; each group was having 10 individuals. Groups 1, 2 and 3 were assigned for 1g, 3g and 6g cinnamon doses/day respectively. Groups 4, 5 and 6 were assigned for 1g, 3g and 6g placebo doses/day respectively. The doses were equally distributed over the day. Cinnamon and placebo were given in the form of capsules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Blood glucose levels of the patients included in the study were measured at the beginning, on the 20th day, and on the 40th day, after consumption. According to the results of the study, it was determined that cinnamon lowered the blood sugar of patients distinctly and significantly [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood glucose levels of the patients included in the study were measured at the beginning, on the 20th day, and on the 40th day, after consumption. According to the results of the study, it was determined that cinnamon lowered the blood sugar of patients distinctly and significantly [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the most discussed effects of cinnamon has been its effect of regulating individuals' insulin resistance and preprandial blood glucose [ 4 6 ]. Cinnamon is also claimed to be a natural insulin stimulant [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…A substance from cinnamon has been isolated and coined as “insulin-potentiating factor” (IPF) [ 102 ], while the antidiabetic effects of cinnamon bark have been shown in streptozotocin-induced diabetic rats [ 33 ]. Several studies have also revealed that cinnamon extracts lower not only blood glucose but also cholesterol levels [ 103 107 ].…”
Section: Antidiabetic Activitymentioning
confidence: 99%
“…Diabetes mellitus is a chronic disorder of glucose metabolism caused by the dysfunction of pancreatic beta cells and insulin resistance. Diabetes is a serious health problem that affects both sexes in all age groups and all over the world [10] . Cinnamon has been shown to have insulin mimetic properties because its biologically active substances enhance glucose uptake by activating insulin receptor kinase activity, autophosphorylation of the insulin receptor, and glycogen synthase activity [11] .…”
Section: Diabetesmentioning
confidence: 99%
“…In one study, a factor called methyl hydroxyl chalcone polymer, which was isolated from cinnamon, was observed to increase insulindependent glucose metabolism approximately 20-fold in vitro. Safdar et al [10] explained that methyl hydroxyl chalcone polymer made fat cells more responsive to insulin by activating the enzyme that causes insulin to bind to cells and inhibiting the enzyme that blocks the process leading to maximal phosphorylation of the insulin receptor, which is associated with increased insulin sensitivity. Cinnamon is rich in polyphenolic components, and it was shown that an intake of 500 mg/d for 12 weeks decreased oxidative stress and improved impaired fasting glucose [12] .…”
Section: Diabetesmentioning
confidence: 99%